AKTIVITAS ANTIOKSIDAN DAN KADAR FENOLIK TOTAL DARI EKSTRAK DAUN KACIP FATIMAH (Labisia pumila) MENGGUNAKAN VARIASI PELARUT EKSTRAKSI - Rahmatullah, Satrio Wibowo; Rizki, Muhammad Ikhwan; Sari, Anna Khumaira; Triyasmono, Liling; Normaidah, Normaidah; Lingga, Herningtyas Nautika (Universitas Borneo Lestari, 2024)
Secondary metabolite content and extract characterization can be influenced by the solvent used in the extraction process. The content of phenolic compounds and antioxidant activity of Labisia pumila leaves can be influenced by solvents. This research aims to determine three extracts' antioxidant activity and total phenolic content using different solvents. Fresh L. pumila leaf samples were cleaned with running water and then dried using a drying cabinet. The dried leaves are then powdered and extracted using distilled water, 70% ethanol, and 96% ethanol. Extraction with distilled water using the infusion method and ethanol using maceration. Next, the solvent obtained was evaporated using a rotary evaporator and oven until a dry extract was obtained. Total phenolic content was determined using the UV-Vis spectrophorometric method with the Folin-Ciocalteu reagent. The standard used is error-free. Antioxidant activity was determined using the DPPH method with a UV-Vis spectrophotometer, then the IC50 value was calculated. The research showed that the total phenolic content of the distilled water extract was 6.437 ± 0.177 w/w GAE, the 70% ethanol extract was 8.377 ± 0.079 w/w GAE, and the 96% ethanol extract was 17.387 ± 0.621% w/w GAE. Antioxidant activity is known to have an IC50 value of distilled water extract of 59,716 ppm, 70% ethanol extract of 50,543 ppm, and ethanol extract of 43,520 ppm. The conclusion of the research is that of the three extracts, it is known that the antioxidant activity is the strongest, and the total phenolics are the highest in the 96% ethanol extract.